THERMAL-CONVERSION BETWEEN DIASTEREOMERIC 1,4-DIPOLAR CYCLOADDUCTS - YOO, KH; KIM, DJ; CHO, JH; KIM, Y; PARK, SW (KOREAN CHEMICAL SOC, 1993)
Thermal conversion between diastereomers formed via 1,4-dipolar cycloaddition was identified by H-1-NMR spectroscopic study depending on temperature and reaction time. Hereupon the formed product by kinetic control was converted to the thermodynamically controlled product. Various diastereomeric 1,4-dipolar cycloadducts were synthesized by the reacting of 5,6-dihydro-3-phenyl-7-[N-phenyl(carbamoyl)]imidazo[2,1-b]thiazolium-betaine with a series of para-substituted phenacyl bromides and the substituent effects were investigated.
Keywords: CYCLOADDITION; HETEROCYCLES